Marriage Validation and Child Marriage: Analysis of the Effectiveness of Law Number 16 of 2019 - Muhammad Kasim; Muhammad Ali; Hasriyanti Hasriyanti (Journal of Law Justice (JLJ), 2026)
This study aims to determine the mechanism of itsbat nikah (marriage validation) for underage marriages conducted without a marriage dispensation based on Law Number 16 of 2019 and to formulate effective and implementable legal solutions in handling cases of child marriage without dispensation through the itsbat nikah mechanism. Method This research was conducted using an empirical juridical approach, which combines various legal sources and materials. The primary legal sources used include interview results and statutory provisions. Meanwhile, secondary legal sources were obtained from relevant scientific articles. Data was collected through interviews and then analyzed qualitatively to gain a deeper understanding of the legal issues under review. The novelty of this research is that it analyzes the mechanism of isbat nikah without dispensation and underage marriage without dispensation. The results of the study show that even though underage marriage without dispensation is a violation of laws and regulations, the court still provides room for marriage validation under certain conditions. The conclusion of the study is that more massive legal socialization from the government and the active role of all parties are needed to prevent the practice of child marriage that does not comply with procedures.